Silica Desiccant Canister: An Unusual Colonic Foreign Body - Rajarajeshwari Ramachandran; Vikash Kumar; Giovannie Isaac-Coss; Denzil Etienne (Case Reports in Gastrointestinal Medicine)
We are reporting a case of incidental identification and removal of two silica desiccant canisters from the cecum in a patient undergoing screening colonoscopy.